Sexual response in the adult male: preliminary study - Rafael Ballester-Arnal; Jesús Castro Calvo; Pedro Salmerón-Sánchez; Vicente Morell-Mengual; Irene Díaz-Rodríguez (INFAD, 2016)
The importance that mature adults give to the fact of having an active sexual behavior is increasing. However, this interest clashes with physical limitations that the old age imposes. The aim of this study was to study sexual behavior among mature adults through the use of one of the most employed questionnaires for its assessment: the International Index of Erectile Function. For this purpose, 38 males between 53 and 81 years old completed the study surveys. We found that whereas some aspects of sexual behavior (e.g., the erectile function or the sexual desire) were adversely affected in mature adults, the impact on other domains such as the global sexual satisfaction is limited. This study increases our knowledge about sexuality in the adulthood and improves our preventive and therapeutic interventions on this collective